Analisis Peran Metaverse Sebagai Media Pendidikan Islam di Masa Depan - Fatoni, Mahfud Heru; Santoso, Baron; Syarifuddin, Hamid; Budiyono, Slamet (Bustanul Ulum Journal of Islamic Education, 2024)
The paper discusses the possibilities role of metaverse as a instructional media of Islamic education in the future. Teaching and learning material of Islamic Education using tecnology would be easier for students to received knowledge from the teacher.The research method used is literature study, by collecting library data from relevant scientific journal sources. The research results show: 1) the metaverse is developing rapidly, considering that the metaverse is an interconnected social network. The implementation of metaverse in the world of Islamic education has a huge opportunity to support the learning process to be better and more enjoyable. 2) Metaverse can create a learning experience that is better, more inclusive, more fun, and more relevant to future demands. 3) Metaverse provides various benefits, including more interactive learning, effective training and development, better customer experience, enabling distance/online learning, enhancing a more enjoyable learning experience, personalizing learning, learning visualization, Game-based learning, Role Play and Perspective taking. 4) By understanding the potential and obstacles of using Metaverse, educators can plan appropriate steps to integrate metaverse technology into modern Islamic education so as to achieve an increase in the quality of Islamic education in Indonesia.